Unraveling cerebrovascular involvement in EGPA through digital subtraction angiography: case presentation and systematic literature review - Viren Vasandani; Sean O’Leary; Ronak Gandhi; Elena Diller; Giri Movva; John Broussard; Vijaya Murthy (BMC Rheumatology)
Abstract Objectives Eosinophilic granulomatosis with polyangiitis (EGPA) involves systemic inflammation of small to medium vessels, with central nervous system (CNS) involvement being rare. While CT (computed tomography) and MRI (magnetic resonance imaging) are standard for diagnosing CNS involvement, digital subtraction angiography (DSA) is infrequently used. We present a unique EGPA case with CNS involvement and review EGPA CNS vascular variations. Methods We present a case of EGPA with CNS involvement, alongside a systematic review of the literature following PRISMA guidelines, querying three databases (PubMed/MEDLINE, SCOPUS, and Science Direct) up to September 2023 for case reports and series on EGPA with CNS involvement. Results A 43-year-old presented with wheezing, multifocal neuropathy, leukocytosis, eosinophilia, positive ANA, and elevated CRP. Imaging revealed lung abnormalities. CT and MRI showed cerebral infarcts. CTA was negative, whereas DSA revealed bilateral segmental narrowing of anterior cerebral artery (ACA) branches and middle cerebral artery (MCA) branches. EGPA was confirmed, and treatment with steroids, cyclophosphamide, and azathioprine, led to remission. A systematic literature review of 27 EGPA cases with CNS involvement found a mean age 54.22 years, with common symptoms including extremity weakness (n = 8) and paresthesia (n = 5). Imaging techniques included MRI (n = 21), CT (n = 11), angiogram (n = 8), MRA (n = 4), CTA (n = 4), and MRV (n = 2), revealing stenosis of the bilateral ACA, vertebral artery, MCA, and basilar artery. Conclusion Our findings suggest a potentially novel role for angiographic imaging in the comprehensive assessment of cerebrovascular involvement in EGPA.